CME Evolution in the Structured Heliosphere and Effects at Earth and Mars During Solar Minimum. Issue 9 (28th September 2022) - Palmerio, Erika; Lee, Christina O.; Richardson, Ian G.; Nieves‐Chinchilla, Teresa; Dos Santos, Luiz F. G.; Gruesbeck, Jacob R.; Nitta, Nariaki V.; Mays, M. Leila; Halekas, Jasper S.; Zeitlin, Cary; Xu, Shaosui; Holmström, Mats; et al.
Abstract: The activity of the Sun alternates between a solar minimum and a solar maximum, the former corresponding to a period of "quieter" status of the heliosphere. During solar minimum, it is in principle more straightforward to follow eruptive events and solar wind structures from their birth at the Sun throughout their interplanetary journey. In this paper, we report analysis of the origin, evolution, and heliospheric impact of a series of solar transient events that took place during the second half of August 2018, that is, in the midst of the late declining phase of Solar Cycle 24. In particular, we focus on two successive coronal mass ejections (CMEs) and a following high‐speed stream (HSS) on their way toward Earth and Mars. We find that the first CME impacted both planets, whilst the second caused a strong magnetic storm at Earth and went on to miss Mars, which nevertheless experienced space weather effects from the stream interacting region preceding the HSS. Analysis of remote‐sensing and in‐situ data supported by heliospheric modeling suggests that CME–HSS interaction resulted in the second CME rotating and deflecting in interplanetary space, highlighting that accurately reproducing the ambient solar wind is crucial even during "simpler" solar minimum periods. Lastly, we discuss the upstream solar wind conditions and transient structures responsible for driving space weather effects at Earth and Mars. Plain Language Summary: The Sun is characterized by a 11‐year periodicity of its levels of activity, resulting in a solar minimum and a solar maximum alternating approximately every 5.5 years. During solar minimum, the Sun and its whole environment are in their simplest configuration, and eruptive events are significantly less frequent. It follows that periods of lower activity are generally considered optimal for tracking solar phenomena from their origin at the Sun throughout their journey in interplanetary space. In this paper, we analyze a series of solar eruptions that took place during the second half of August 2018 and follow them until their arrival at Earth and Mars, taking into account their associated effects on the two planets. We find that, even during solar minimum, the large‐scale structure of the solar and interplanetary environment can have more or less dramatic impacts on the evolution of eruptions as they travel away from the Sun. Additionally, we suggest that the same event can cause diverse levels of disturbances at different planets, depending on the particular structure and properties of the impacting solar wind. Key Points: We analyze the eruption and propagation of two coronal mass ejections (CMEs) from the Sun up to Earth and Mars during August 2018 Both CMEs were observed at Earth, but the second missed Mars, possibly due to interaction with a following high‐speed solar wind stream The sequence of events observed resulted in a strong magnetic storm at Earth, but only moderate disturbances at Mars